Blood eosinophilia and ulcerative colitis–influence of ethnic origin. Issue 734 (December 1986) - Benfield, G. F.; Asquith, P.
Abstract : Blood eosinophilia is an alleged manifestation of ulcerative colitis. To investigate this association and to determine the effect of race, the occurrence of eosinophilia in all 44 Asians presenting between 1968-84 was compared to that in an age- and sex-matched group of indigenous white Caucasian patients presenting over the same period. Nineteen (43%) of the Asians presented with an eosinophilia compared to only 3 Caucasians (P less than 0.0001); similar numbers (14 and 13) in both groups demonstrating transient eosinophilia on occasions during maintenance treatment although not related to clinical relapse. A control group of Asians with other disorders not known to be associated with eosinophilia did not manifest this abnormality on presentation although 3 patients did so transiently during out-patient observation. Eosinophilia is a feature of ulcerative colitis in many Asians possibly due either to an unusual racial response to ulcerative colitis or as a reflection of the underlying pathogenesis of their disease. We have not confirmed earlier suggestions of such a feature in white Caucasians. Eosinophilia occurring during maintenance treatment in both groups may be drug-related.